2021
DOI: 10.1051/e3sconf/202127308027
|View full text |Cite
|
Sign up to set email alerts
|

Specifics of the legal regulation of environmental management in agriculture

Abstract: It is difficult to overestimate the importance of agriculture, its effectiveness for the economic and socio-political sector of development of any state in the modern world. However, agriculture relies on the use of natural resources in its activities - land, soil, water, atmospheric air, forests and other vegetation. The quality of these natural components of the natural environment directly affects the functioning and productivity of agricultural organizations. Environmental pollution problems are complex pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…The comparative analysis has shown that differences in standards hinder objective forecasts for the development of sustainable agriculture in different countries [2]. Analysts of agrarian law note the dynamics of the growth of legal norms for the transition to organic agricultural products [3].…”
Section: Substantiation Of the Relevance And Novelty Of The Studymentioning
confidence: 99%
“…The comparative analysis has shown that differences in standards hinder objective forecasts for the development of sustainable agriculture in different countries [2]. Analysts of agrarian law note the dynamics of the growth of legal norms for the transition to organic agricultural products [3].…”
Section: Substantiation Of the Relevance And Novelty Of The Studymentioning
confidence: 99%